Acoustic Emission (Ae) Techniques For The Damage Assessment Of Structures. - Muhamad Bunnori, Nor Azura; Johari, Megat Azmi; Kabir, Shahid (Universiti Sains Malaysia, 2012)
Reinforced concrete (RC) has been facing several types of damage mechanism during their lifetime. The types of common defects in concrete structures are crack formation, corrosion, scalling and etc. Therefore a non destructive evaluation method such as Acoustic Emission (AE) is required for assessing the condition of the RC structures. AE testing in RC structures shows great potential in monitoring and assessing the health conditions of structures. AE is used as a tool to detect, identify, locate and quantify a variety of damage mechanism.